2021
DOI: 10.1126/scitranslmed.abb0122
|View full text |Cite
|
Sign up to set email alerts
|

Graft-derived extracellular vesicles transported across subcapsular sinus macrophages elicit B cell alloimmunity after transplantation

Abstract: Despite the role of donor-specific antibodies (DSAs) in recognizing major histocompatibility complex (MHC) antigens and mediating transplant rejection, how and where recipient B cells in lymphoid tissues encounter donor MHC antigens remains unclear. Contrary to the dogma, we demonstrated here that migration of donor leukocytes out of skin or heart allografts is not necessary for B or T cell allosensitization in mice. We found that mouse skin and cardiac allografts and human skin grafts release cell-free donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…These changes are certainly linked to a function of the EV compartment in the process of graft rejection. EVs are a potent intermediate that promotes contact between donor antigens and the host immune system, as they are enriched in MHC and costimulatory molecules for most types of transplant rejection (139,(141)(142)(143).…”
Section: Discussionmentioning
confidence: 99%
“…These changes are certainly linked to a function of the EV compartment in the process of graft rejection. EVs are a potent intermediate that promotes contact between donor antigens and the host immune system, as they are enriched in MHC and costimulatory molecules for most types of transplant rejection (139,(141)(142)(143).…”
Section: Discussionmentioning
confidence: 99%
“…Gunasekaran et al showed expression of donor HLA and lung associated self-antigens on EV from serum and bronchoalveolar lavage fluid of lung transplant recipients with acute rejections but not in recipients with stable transplant ( 43 , 44 ). Few studies in various transplant models have shown that transfer of donor HLA to recipient APCs via EV is involved in the perpetuation of alloresponses by T cells leading to graft dysfunction ( 14 , 37 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the uptake of these vesicles to SSM and MSM in LNs plays a key role in immune suppression or tolerance [27], whereas the role of MCM has not been reported yet [28]. However, another report revealed that allograft-derived extracellular vesicles enhanced the immunity in the donor, and then consequently induced the rejection of allograft [29]. The precise role of this PS-mediated uptake is currently controversial.…”
Section: Discussionmentioning
confidence: 99%